Understanding Immune‐Driven Brain Aging by Human Brain Organoid Microphysiological Analysis Platform. Issue 27 (31st July 2022) - Ao, Zheng; Song, Sunghwa; Tian, Chunhui; Cai, Hongwei; Li, Xiang; Miao, Yifei; Wu, Zhuhao; Krzesniak, Jonathan; Ning, Bo; Gu, Mingxia; Lee, Luke P.; Guo, Feng
Abstract: The aging of the immune system drives systemic aging and the pathogenesis of age‐related diseases. However, a significant knowledge gap remains in understanding immune‐driven aging, especially in brain aging, due to the limited current in vitro models of neuroimmune interaction. Here, the authors report the development of a human brain organoid microphysiological analysis platform (MAP) to discover the dynamic process of immune‐driven brain aging. The organoid MAP is created by 3D printing that confines organoid growth and facilitates cell and nutrition perfusion, promoting organoid maturation and their committment to forebrain identity. Dynamic rocking flow is incorporated into the platform that allows to perfuse primary monocytes from young (20 to 30‐year‐old) and aged (>60‐year‐old) donors and culture human cortical organoids to model neuroimmune interaction. The authors find that the aged monocytes increase infiltration and promote the expression of aging‐related markers (e.g., higher expression of p16) within the human cortical organoids, indicating that aged monocytes may drive brain aging. The authors believe that the organoid MAP may provide promising solutions for basic research and translational applications in aging, neural immunological diseases, autoimmune disorders, and cancer. Abstract : The development of a human brain organoid microphysiological analysis platform to model immune–brain interaction is reported and the monocytes found from aged donors may drive brain aging.